IL-6/NOS2 inflammatory signals regulate MMP-9 and MMP-2 activity and disease outcome in nasopharyngeal carcinoma patients - Zergoun, Ahmed-Amine; Zebboudj, Abderezak; Sellam, Sarah Leila; Kariche, Nora; Djennaoui, Djamel; Ouraghi, Samir; Kerboua, Esma; Amir-Tidadini, Zine-Charaf; Chilla, Dalia; Asselah, Fatima; Touil-Boukoffa, Chafia; Merghoub, Taha; et al. (Tumor biology, 2016)
The role of nitric oxide (NO) · in the development of the metastatic properties of nasopharyngeal carcinoma (NPC) is not fully understood. Previous studies proposed that interleukin-6 (IL-6) would act as regulator of matrix metalloprotease activation in NPC. Recently, we showed that (NO) · was a critical mediator of tumor growth in patients. The aim of this study was to determine the implication of IL-6 in the progression of NPC pathology via metalloprotease (MMP) activation and their possible correlation with (NO) · production. We observed a significant increase in IL-6 and nitrite (NO 2 − ) synthesis in patients ( n = 17) as well as a strong expression of IL-6 and nitric oxide synthase 2 (NOS2) in the analyzed tumors ( n = 8). In patients’ plasma, a negative correlation associated IL-6 with circulating nitrites ( r = −0.33). A negative correlation associated the H-scores of these signals in the tumors ( r = −0.47). In patients’ plasma, nitrite synthesis was positively associated with MMP-9 activation ( r = 0.45), pro-MMP-2 expression ( r = 0.37), and negatively correlated with MMP-2 activation ( r = −0.51). High nitrite levels was associated with better recurrence-free survival (RFS) ( p = 0.02). Overall, our results suggest that the IL-6/NOS2 inflammatory signals are involved in the regulation of MMP-9- and MMP-2-dependent metastatic activity and that high circulating nitrite levels in NPC patients may constitute a prognostic predictor for survival.